Glass [videorecording (DVD)] - Shyamalan, M. Night; McAvoy, James, 1979-; Willis, Bruce, 1955-; Taylor-Joy, Anya, 1996-; Jackson, Samuel L (Universal Pictures Home Entertainment, 2019)
For one special security guard, tracking people down is a paranormal sort of hobby. Able to use his rare abilities to find people, David Dunn is suddenly given a job that seems more daunting than all the others before it. He'll need to find Kevin Wendell Crumb, and time is of the essence. But part of the problem is that Crumb is an extremely disturbed man and with 24 personalities, he's a lot more complicated than the others Dunn has found.